Effects of Biphenyldimethyl-dicarboxylate Administration Alone or Combined with Silymarin in the CCL4 Model of Liver Fibrosis in Rats - Omar M. E. Abdel-Salam; Amany A. Sleem; Fatma A. Morsy (The Scientific World Journal)
The effect of biphenyldimethyldicarboxylate (DDB), a synthetic compound, in use for the treatment of chronic hepatitis was studied on hepatic injury caused in rats by administration of carbon tetrachloride (CCl4). Starting at time of administration of the first dose of CCl4, rats received DDB at four dose levels (3, 15, 75 or 375 mg/kg), silymarin (22 mg/kg), a combination of DDB (75 mg/kg) and silymarin (22 mg/kg) or saline (control) once orally daily for 30 days. The administration of DDB in CCl4-treated rats at 75 or 375 mg/kg resulted in 61.2-76.2% decrease in alanine aminotransferase (ALT) and 46.9-60.8% decrease in aspartate aminotransferase (AST), respectively compared with the CCl4 control group. Silymarin treatment resulted in 34.6 and 30% decrease in ALT and AST, while DDB (75 mg/kg) combined with silymarin (22 mg/kg) resulted in 58.2 and 31% decrease in ALT and AST, respectively. Serum creatinine increased by 50% by DDB at 375 mg/kg. After treatment with DDB at 75 or 375 mg/kg or DDB combined with silymarin, the development of liver necrosis and fibrosis caused by CCl4 was markedly reduced, while after DDB combined with silymarin no DNA aneuploid cells could be observed. The decrease in glycogen and protein contents in hepatocytes caused by CCl4 was markedly prevented by co-treatment with DDB at 75 or 375 mg/kg or DDB combined with silymarin. It is concluded that in the model of hepatic injury caused by chronic administration of CCl4 in rats, the synthetic compound DDB, limits hepatocellular injury and exerts antifibrotic effect. Better improvement in protein, DNA, mucopolysaccharide content was seen after both DDB and silymarin compared to DDB alone. It is suggested, therefore, that DDB alone or in combination with silymarin might prove of benefit in the therapy of chronic liver disease. Monitoring of kidney functions in patients taking DDB is warranted.